2015
DOI: 10.1002/2015jf003630
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of wave‐supported fluid‐mud generation and deposition on an active continental margin

Abstract: Wave‐supported fluid muds (WSFM) are a type of gravity flow that can rapidly transport sediment across continental margins. They occur when wave‐induced bed stress maintains suspended‐sediment concentrations (SSC) >10 g L−1, and sediment‐induced stratification near the top of the wave boundary layer limits upward diffusion of sediment. Observations from near‐bed instrumentation are used to evaluate the conditions under which WSFMs form on the continental shelf offshore of the Waipaoa River, NZ. An event in Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 91 publications
(230 reference statements)
6
36
0
Order By: Relevance
“…Bottom stresses remained elevated for almost 2 days and reached values well above the threshold of resuspension for silts and fine sands. Following the large stresses, sediment concentration profiles measured by the ABSs showed maximum near‐bottom concentrations of 40 (g/L) and 50 (g/L) at the 12 and 8 m sites (Figures b and c), respectively, which are of similar magnitude to those of previously reported WSGF events (Hale & Ogston, ; Traykovski et al, ). Peak concentrations of 10 (g/L) were reported by the OBS 20 cmab at the 8 m site (Figure b), suggesting that at times the high‐concentration layer was at least 15–20 cm thick.…”
Section: Observations and Resultssupporting
confidence: 84%
“…Bottom stresses remained elevated for almost 2 days and reached values well above the threshold of resuspension for silts and fine sands. Following the large stresses, sediment concentration profiles measured by the ABSs showed maximum near‐bottom concentrations of 40 (g/L) and 50 (g/L) at the 12 and 8 m sites (Figures b and c), respectively, which are of similar magnitude to those of previously reported WSGF events (Hale & Ogston, ; Traykovski et al, ). Peak concentrations of 10 (g/L) were reported by the OBS 20 cmab at the 8 m site (Figure b), suggesting that at times the high‐concentration layer was at least 15–20 cm thick.…”
Section: Observations and Resultssupporting
confidence: 84%
“…Jaramillo et al () reported 3 5 cm/s for WSGF events observed at Atchafalaya shelf. Through indirect estimate of the sediment flux budget, Hale and Ogston () obtained lower values of WSGF velocity of 2 3 cm/s on the continental shelf offshore of the Waipaoa River. However, the shelf slope in these later two field sites is milder ( 0.003) than that reported by Traykovski et al ().…”
Section: Discussionmentioning
confidence: 99%
“…A key uncertainty of the transport lies in the magnitude of the cross-shelf (downslope) gravity current speed. A literature survey suggests that, although WSGFs have been observed in many continental shelves (e.g., Hale & Ogston, 2015;Jaramillo et al, 2009;Traykovski et al, 2000Traykovski et al, , 2007Traykovski et al, , 2015, the cross-shelf current speed differs by several factors, ranging from a few to tens of cm/s. Moreover, different from typical turbidity current, field data show that WSGF requires persistent wave energy to generate sufficient fluid turbulence in the WBBL, which supports the suspended sediments (Hale & Ogston, 2015;Traykovski et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Three primary means, i.e., (a) surface buoyancy plume (hypopycnal) dispersal, (b) dilute suspension dispersal in the bottom‐boundary layer, and (c) gravity‐driven turbidity (hyperpycnal) flows have been suggested to be responsible for transporting fine‐grained sediment (mud to fine sand) across continental shelves [ Walsh and Nittrouer , ]. Whilst the first two means of sediment transport have been documented extensively [e.g., McCave , ; Colby , ; Wright , ; Cacchione et al ., ; Fredsoe and Deigaard , ; Nielsen , ; van Rijn , ; Nittrouer and Wright , ; Bursik , ; Bennett et al ., ; Syvitski and Morehead , ; Hill and McCave , ; Geyer et al ., ; McKee et al ., ; Moriarty et al ., ], mechanisms for triggering and maintaining a gravity‐driven turbidity flow on relatively flat (slope less than 0.012) continental shelves and its quantitative contribution to across‐shelf sediment transport have recently started to attract considerable interest [e.g., Trowbridge and Kineke , ; Kineke et al ., ; Sternberg et al ., ; Ogston et al ., ; Traykovski et al ., ; Wright et al ., ; Scully et al ., ; Friedrichs and Wright , ; Dalrymple and Cummings , ; Harris et al ., ; Hsu et al ., ; Macquaker et al ., ; Ozdemir et al ., ; Corbett et al ., ; Kampf and Myrow , ; Hale and Ogston , ; Hooshmand et al ., ].…”
Section: Introductionmentioning
confidence: 99%